2020
DOI: 10.1038/s41598-020-75492-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term hydrogen intervention on the physiological function of rats

Abstract: The potential therapeutic effects of molecular hydrogen (H2) have now been confirmed in various human and animal-disease models. However, the effects of H2 on the physiological function in a normal state have been largely neglected. Hydrogen-rich water (HRW) intake and hydrogen inhalation (HI) are the most common used methods for hydrogen administration, the difference in the effects between HRW intake and HI remains elusive. In the present study, the body weight and 13 serum biochemical parameters were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
7
20
0
Order By: Relevance
“…Long-term H 2 intervention reduced the body weight of rats in the HI group (455.20 ± 31.57 g), while no significant changes were observed in the HRW group (498.80 ± 18.50 g) compared to controls (525.00 ± 17.78 g) (Fig. 2 A) 24 . Visceral fat volume (HRW: 7760 ± 429 mm 3 ; HI: 6260 ± 1624 mm 3 ; CTRL: 13,960 ± 4138 mm 3 ) (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Long-term H 2 intervention reduced the body weight of rats in the HI group (455.20 ± 31.57 g), while no significant changes were observed in the HRW group (498.80 ± 18.50 g) compared to controls (525.00 ± 17.78 g) (Fig. 2 A) 24 . Visceral fat volume (HRW: 7760 ± 429 mm 3 ; HI: 6260 ± 1624 mm 3 ; CTRL: 13,960 ± 4138 mm 3 ) (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…We recently found that H 2 -treated rats (HRW and HI) had reduced serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bile acid (TBA) 24 , suggesting that prolonged exposure to H 2 could influence liver physiology and functions. To study the global effects of long-term H 2 treatment on the liver, we performed an RNA sequencing (RNA seq) analysis of liver tissues collected from untreated rats (Control group), rats given hydrogen-rich water (HRW) or inhaled 4% H 2 (HI) 2 h daily for 6 months (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the aims of the present study was to explore the possible regulatory effects of long term of HRW intake and hydrogen inhalation on gut microbiome. Our previous study showed that long term of HRW intake or hydrogen inhalation can influence some serum biochemical parameters of normal rats, indicating the potential modulatory effect of hydrogen consumption on metabolism in health status [8]. To further investigate the effect of hydrogen consumption on metabolism, LC-MS based pseudotargeted metabolomics analysis was performed to determine the changes in the levels of plasma metabolites.…”
Section: Introductionmentioning
confidence: 99%